Effects of Paeoniae Radix Rubra on lowering lipid via bioinformatics and gut microbiome - Zhi Lin; Haiqing Luo; Shuang Pan; Yvmo Li; Xinrui Zhou; Jiarui Zhao; Xinyi Xu; Xiaowen Li; Yuchen Wang; Guangfu Lv; Zhe Lin; He Lin; et al. (Scientific Reports)
Abstract Hyperlipidemia, a metabolic disorder characterized by abnormal lipid levels, is closely linked to an increased risk of cardiovascular disease. In this study, we investigated the hypolipidemic properties of Paeoniae Radix Rubra and its regulatory effects on gut microbiota composition in a high-fat diet model. Using UHPLC-QE-MS/MS, we identified its chemical constituents and applied bioinformatics, network pharmacology, and molecular docking to virtually screen for bioactive compounds and molecular targets. Gelomulide N and (E)-5-[(1 S,4aR,8aR)-2-formyl-5,5,8a-trimethyl-1,4,4a,6,7,8-hexahydronaphthalen-1-yl]-3-(acetoxymethyl)pent-2-enoic acid were identified as potential active compounds. Paeoniae Radix Rubra exhibited notable hypolipidemic, hepatoprotective, and gut microbiota-restoring effects, potentially influencing the mevalonate pathway by interacting with proteins such as P53, HMGCR, and SREBP2, which may contribute to reduced cholesterol synthesis. These findings indicate that the Paeoniae Radix Rubra could serve as a potential therapeutic strategy for hyperlipidemia, possibly mediated through modulation of lipid metabolism pathways and gut microbiota remodeling.